2021
DOI: 10.20515/otd.982243
|View full text |Cite
|
Sign up to set email alerts
|

Are Covid-19 Pandemic Physical Activity Levels Affect Balance, Gait, Cognitive Functions and Fear of Covid-19 of Older Adults?

Abstract: The aim of this study is to compare the balance, gait, cognitive functions and fear of in older adults according to physical activity levels (PALs) and investigate the relationship between PALs and balance, gait, cognitive functions and FoC-19 of older adults in times of Covid-19 pandemic. 40 healthy older adults were divided into two groups as low and high PALs groups according to their median score on the Physical Activity Scale for the Elderly. Outcome measures included the Berg Balance Scale, Timed Up and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It has been found that decreased healthy life behaviors, such as physical activity, correlated with the fear of COVID-19 in the elderly. [ 18 ] Diminished interest and avoidance of news about COVID-19 are related to younger age, greater post-traumatic stress symptoms, less fear of COVID-19, and less frequent use of professional healthcare devices. In addition, it has been shown that coronavirus anxiety may not increase as feared in the increased exposure to information from the media, and education level is the main risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that decreased healthy life behaviors, such as physical activity, correlated with the fear of COVID-19 in the elderly. [ 18 ] Diminished interest and avoidance of news about COVID-19 are related to younger age, greater post-traumatic stress symptoms, less fear of COVID-19, and less frequent use of professional healthcare devices. In addition, it has been shown that coronavirus anxiety may not increase as feared in the increased exposure to information from the media, and education level is the main risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…7 The literature demonstrated that low activity levels exacerbated fear of COVID-19 among older adults. 8 However, those regularly engaging in vigorous and moderate-vigorous physical activity during quarantine showed higher resilience, positive affect, and lower depression. 9 Social support became critical for preserving physical and mental health amid the pandemic.…”
Section: Introductionmentioning
confidence: 98%
“…Reduced physical activity and less social interaction during the pandemic also adversely affected their psychological well‐being 7 . The literature demonstrated that low activity levels exacerbated fear of COVID‐19 among older adults 8 . However, those regularly engaging in vigorous and moderate‐vigorous physical activity during quarantine showed higher resilience, positive affect, and lower depression 9 …”
Section: Introductionmentioning
confidence: 99%